Cost savings associated with an outpatient otolaryngology telemedicine clinic. Issue 2 (14th January 2019) - Philips, Ramez; Seim, Nolan; Matrka, Laura; Locklear, Brittany; Moberly, Aaron C.; Inman, Mark; Essig, Garth
Abstract : Objective: To test the null hypothesis that there is no difference in patient cost savings between the telemedicine and traditional face‐to‐face approach. The second objective was to assess the financial impact on the peripheral healthcare system, as compared with staffing a conventional clinic with "on‐site" otolaryngologist. Methods: Twenty‐one patients were enrolled. To assess "patient‐benefit" cost savings, a model was formulated that would utilize a certified nurse practitioner (CNP) to conduct a general otolaryngology clinic at the peripheral site, as compared with having to travel to the tertiary referral center. A "peripheral site‐benefit" cost analysis was performed to assess costs of initiating and operating a telemedicine clinic at the peripheral site, compared with having an on‐site otolaryngologist. Results: The total patient‐benefit cost savings would be $182.09 per patient per encounter and $333.22 per patient annually. The fixed cost to the peripheral site to initiate the telemedicine system was $9, 895. Two hundred sixty telemedicine encounters would be needed to offset the initial cost, and 537 encounters would be needed to surpass revenue of the conventional clinic. Conclusion: A real‐time telemedicine otolaryngology clinic provides significant cost savings for both patients and the peripheral healthcare system. This pilot study supports telemedicine as a cost‐effective approach to providing general otolaryngology care to rural patients. Level of Evidence: 4